2023
DOI: 10.1007/s12520-023-01789-2
|View full text |Cite
|
Sign up to set email alerts
|

Production method of the Königsaue birch tar documents cumulative culture in Neanderthals

Abstract: Birch tar is the oldest synthetic substance made by early humans. The earliest such artefacts are associated with Neanderthals. According to traditional interpretations, their study allows understanding Neanderthal tool behaviours, skills and cultural evolution. However, recent work has found that birch tar can also be produced with simple processes, or even result from fortuitous accidents. Even though these findings suggest that birch tar per se is not a proxy for cognition, they do not shed light on the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…Looking forward, larger and more diverse datasets can feed and refine in-silico models like ours to answer questions that are difficult to explore with individual experimental designs. In that light, we are happy to see that recent experimental and archaeological work by Schmidt and Tennie 18 confirms our theoretical expectations about the evolution of technology.…”
Section: Discussionsupporting
confidence: 61%
“…Looking forward, larger and more diverse datasets can feed and refine in-silico models like ours to answer questions that are difficult to explore with individual experimental designs. In that light, we are happy to see that recent experimental and archaeological work by Schmidt and Tennie 18 confirms our theoretical expectations about the evolution of technology.…”
Section: Discussionsupporting
confidence: 61%
“…We therefore attempted to identify other possible performance gains of a high ochre load in bitumen. It is known from Neanderthal birch tar finds ( 5 , 32 ) that adhesives were used as handles directly attached to stone tools (as opposed to being used for hafting stone tools to wooden handles or shafts). We therefore molded handles of fresh bitumen to stone tools ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, what are the implications if these compound adhesives were made by Neanderthals? It has recently been shown that Neanderthal birch tar making relied on the cumulative cultural transmission of techniques ( 32 ). This was proposed to be one of the core criteria for understanding ancient adhesives as proxies of evolutionary processes ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was not claimed that the amount of cobbles tested in that study (three) were actually used—and in this way—by Neanderthals. And indeed, it has recently been shown 6 that Neanderthals made birch tar with an elaborate underground technique that was most likely the improvement of an earlier aboveground technique. Thus, a specific claim that the condensation method “likely needed to be scaled up” 2 is not rooted in archaeological data.…”
Section: The Need Of “Scaling Up” the Condensation Methodsmentioning
confidence: 99%